STRUCTURE OF UTILIZATION OF LIVING DIVERSITY OF WILD ANIMAL BY COMMUNITY IN COASTAL AREA OF TOMU DISTRICT, TELUK BINTUNI DISTRICT, PAPUA BARAT - Mokhamad Asyief Khasan Budiman; Yoppie Christian (COJ (Coastal and Ocean Journal), 2018)
Tomu District is one of the areas in the coastal district of Teluk Bintuni, West Papua. The accelerated development that continues to develop will significantly affect the existence of wildlife in the Tomu District. The purpose of this study was to identify the diversity and distribution of coastal wildlife in Tomu district. In addition, this study wants to identify the structure of its use by the community. The study was conducted in Tomu District, Bintuni Bay Regency in January 2017. The method used was rapid observation in three sample points as representatives of three habitat types. In addition, interviews were conducted with community representatives in the Tomu District. The results showed that there were 44 species of birds, 3 types of mammals, and 5 types of herpetofauna found during the study. Based on information from the community, 3 species of animal were found in the study area but were not found during the study. The utilization structure by the community consists of the utilization of direct values (economic / recreation) and non-use value (conservation) and there is no utilization to take indirect values from their biological wealth. Keywords: Tomu District, biodiversity, wildlife, utilization structure, Bintuni Bay